Multiscale analysis of active region evolution - Hewett, R; Gallagher, P; McAteer, R; Young, C; Ireland, J; Conlon, P; Maguire, K (2008)
Flows in the photosphere of solar active regions are turbulent in nature. Because magnetic fields are frozen into the plasma on the solar surface, magnetograms can be used to investigate the processes responsible for structuring active regions. Here, a continuous wavelet technique is developed, analyzed, and used to investigate the multiscale structure of an evolving active region using magnetograms obtained by the Michelson Doppler Imager (MDI) onboard the Solar and Heliospheric Observatory (SOHO). The multiscale structure was measured using a 2D continuous wavelet technique to extract the energy spectrum of the region over the time scale of 13 days. Preliminary evidence of an inverse cascade in active region NOAA 10488 is presented as well as a potential relationship between energy scaling and flare productivity. © 2007 Springer Science+Business Media B.V.